PARTICIPATION OF THE REPUBLIC OF KOREA IN THE DEVELOPMENT OF THE ARCTIC: PROSPECTS AND CONTRADICTIONS - Aleksandr Ivanovich Shadrin; Young Jun Baek; Jong-man Han (Наука Красноярья, 2019)
The current Arctic study is of great importance. However, insufficient attention has been paid to the problems of interaction between Russian and Republic of Korea in the area of development and scientific & educational communities on these regions. This study focuses on the assessment of resource potential, transport and logistics of the Russian Arctic.